Correlation between preoperative predictions and surgical findings in the parotid surgery for tumors. Issue 1 (December 2016) - Vaiman, Michael; Luckman, Judith; Sigal, Tal; Bekerman, Inessa
Abstract Background To compare preoperative CT/MRI based predictions with real surgical findings for deep lobe parotid gland surgery. Methods The study analyzed 122 parotidectomies (2004–2014) for benign tumor removal. The facial nerve, the Utrecht line, the Conn's arc, and the retromandibular vein were used as landmarks for CT/MRI presurgical evaluation of patients. We assessed 106 CT images and 86 MRI images. The study compared preoperative evaluation of tumor location with its actual location that was revealed during the operation and assessed the importance of the landmarks. Results In general, the agreement between preoperative CT prediction and actual location of the parotid tumors was achieved in 88.7 % (n = 94/106) when facial nerve line was used as a landmark. However, out of 14 tumors in the deep lobe only 5 were located correctly (35.7 %). Of the other existing CT landmarks, none showed more precision over others. The agreement between MRI based prediction and surgical results on actual location of the tumor was achieved in 94.2 %. Out of 12 MRI-investigated tumors in the deep lobe nine were located correctly that gives 75 % agreement with surgical results. Conclusion Our data suggests that no existing CT landmark can be accepted as completely reliable in cases when selective deep lobe parotidectomy is planned. If tumor location is suspected in the deep lobe of the gland, MRI imaging is necessary to confirm the diagnosis. An operating surgeon should be prepared that in some cases the true location of the tumor would be revealed only during surgery.